2015
DOI: 10.1080/1540496x.2015.1103138
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality, Trade Openness, and Financial Sector Development in Asia: An Empirical Investigation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 43 publications
9
96
0
2
Order By: Relevance
“…The main basis of this test is N>T principle. In the study, there are 18 periods/years (T) which cover 2012:12-2017:03 and 87 firms (N), therefore Pesaran (2004) CDLM test's conditions were provided (Wu, Liu and Hsueh, 2016, p. 114) (Le, Kim andLee, 2016, p. 1053) (Hepaktan & Çınar, 2012, p. 48-49). Stationary of series was tested by unit root tests.…”
Section: Data Set and The Methodologymentioning
confidence: 99%
“…The main basis of this test is N>T principle. In the study, there are 18 periods/years (T) which cover 2012:12-2017:03 and 87 firms (N), therefore Pesaran (2004) CDLM test's conditions were provided (Wu, Liu and Hsueh, 2016, p. 114) (Le, Kim andLee, 2016, p. 1053) (Hepaktan & Çınar, 2012, p. 48-49). Stationary of series was tested by unit root tests.…”
Section: Data Set and The Methodologymentioning
confidence: 99%
“…Law and Demetriades (2006), Law (2007), Baltagi et al (2009), Law (2009, Acikgoz et al (2012), Zhang et al (2015), Onanuga and Onanuga (2016)), while some papers found that only trade or financial openness had positive effect on development of financial sectors (e.g. see Kim et al (2010), Le et al (2016), Muhammad et al (2016)). However some papers have revealed that there is no significant interaction amid financial/trade openness and development of financial sector (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So their findings are in favor of SOH. Le et al (2016) researched the determinants of financial development in 26 Asian countries during the 1995-2011 period employing dynamic panel regression and revealed that trade openness affected financial development positively in developed countries, but had no impact in developing countries. In another study, Muhammad et al (2016) researched the interplay between development of financial sector and trade openness in Pakistan over the period 1971 and 2011 using Johansen cointegration and Granger Causality test and revealed that trade openness affected financial development positively and a one dimensional causality from trade openness to financial development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The existing literature on the subject of finance-growth recognizes that financial development enhances the capital supply and at the same time facilitates the distribution of financial resources to the most productive investments, which further implies growth in the economy of any country (Roubini & Sala-i-Martin, 1992; Le et al, 2016). Since the early 1990s, the financial industry has attracted conspicuous debate concerning the role it has in the course of economic development (Armenta, 2007).…”
Section: An Overview Of the Industry Under Studymentioning
confidence: 99%